Functional characterisation of Arabidopsis genes encoding members of the AP2/ERF transcription factor family - Brennan, Sínead (Trinity College (Dublin, Ireland). Department of Genetics, 2005)
The EU Framework 5 REGIA (Regulatory Gene Initiative in Arabidopsis) Consortium, comprising 29 laboratories, was established to investigate transcription factor gene function in Arabidopsis. As part of the REGIA project, the present study describes the characterisation, in terms of sequence, expression and function, of two members of the plant-specific AP2/ERF transcription factor family: AP2.76 and AP2.72. Phylogenetic analyses of their predicted amino acid sequences placed AP2.76 in the DRE/CRT subgroup, members of which bind the DRE/CRT cis-acting element and AP2.72 in the ERF subgroup, members of which bind the GCC-box cis-acting promoter element. On the basis of the observed sequences similarities and predicted DNA binding specificities, AP2.76 was hypothesised to function in an abiotic stress signalling pathway while AP2.72 was hypothesized to function in a pathogen response pathway.
Keywords: Genetics, Ph.D.; Ph.D. Trinity College Dublin